Pengaruh Literasi Keuangan dan Gaya Hidup terhadap Perilaku Keuangan Karyawan di Kabupaten Sumbawa - Abdul Salam; Asrul Syani (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the effects of financial literacy and lifestyle on the financial behavior of Indomaret employees in Sumbawa Regency. Sound financial behavior plays a crucial role in achieving financial well-being, particularly amid increasingly complex living needs and shifting consumption patterns. This study employed a quantitative descriptive approach using a purposive sampling technique involving 100 Indomaret employees. Data were collected through a structured questionnaire based on a five-point Likert scale and analyzed using multiple linear regression after satisfying the classical assumption tests, including normality, heteroscedasticity, and multicollinearity. The findings reveal that financial literacy has a positive and statistically significant effect on financial behavior, as indicated by a regression coefficient of 0.210, a t-value of 2.799, and a significance level of 0.006 (p less than 0.05). In contrast, lifestyle does not significantly influence financial behavior, as reflected by a regression coefficient of -0.032, a t-value of -0.293, and a significance level of 0.770 (p greater than 0.05). The coefficient of determination (Adjusted R-Square = 0.056) indicates that financial literacy and lifestyle jointly explain only 5.6% of the variance in financial behavior, while the remaining 94.4% is attributable to other factors beyond the research model. These findings highlight that financial literacy is a key determinant of rational, disciplined, and responsible financial behavior, whereas lifestyle is not a dominant factor in employees' financial management. Therefore, companies and policymakers should strengthen financial literacy education programs to enhance employees' financial decision-making quality and long-term financial resilience.